Analysis of the Forbush Decreases and Ground‐Level Enhancement on September 2017 Using Neutron Spectrometers Operated in Antarctic and Midlatitude Stations. Issue 1 (24th January 2019) - Hubert, G.; Pazianotto, M. T.; Federico, C. A.; Ricaud, P.
Abstract: This work investigates solar events occurred in September 2017 characterized by a series of Forbush decreases and a ground level enhancement (GLE). Forbush decreases is a rapid decrease in the observed https://en.wikipedia.org/wiki/Galactic_cosmic_ray intensity following a coronal mass ejection while GLE is induced by a strong solar event for which the flux of high‐energy solar particles is sufficient to enhance the radiation level on the ground. These investigations were performed using data recorded by a neutron spectrometer network composed of a Bonner sphere system. Two instruments located at Pic‐du‐Midi Observatory (+2, 885 m above sea level) and at Concordia station (Antarctica, +3, 233 m) record simultaneously and continuously the neutron spectra, allowing to consider short‐term variations during solar events. The main objective is to analyze neutron spectral properties including their energy distributions and dynamics. This paper presents cosmic ray‐induced neutron spectra during active solar event leading to changes in the local cosmic ray spectrum (Forbush decreases and a GLE). Concerning the GLE, analyses show that neutrons in the evaporation domain are particularly amplified during the GLE, while other energetic domains increase uniformly. Key Points: This paper presents an analysis of neutron spectrum variations during solar event of September 2017 Investigations are based on data recorded by a neutron spectrometer network (midlatitude and Antarctica stations) The peak of evaporation is particularly amplified during the GLE